Evaluation of Antibacterial and Antibiofilm Properties of Kojic Acid against Aeromonas sobria and Staphylococcus saprophyticus. (5th January 2023) - Ye, Jing-Xin; Qian, Yun-Fang; Lan, Wei-Qing; Xie, Jing
Abstract : Biofilms composed of microbes and extracellular polymeric substances (EPSs) pose a significant risk to human health and lead to economic loss in the food industry. In this study, the antimicrobial and antibiofilm properties of kojic acid (KA) against Aeromonas sobria ( A. sobria ) and Staphylococcus saprophyticus ( S. saprophyticus ) were investigated by determining the leakage of DNA and protein, cell morphology, biofilm formation, the metabolic activity of biofilms, excretion of EPS, and biofilm architecture. The results indicated that the values of minimum inhibitory concentration (MIC) of A. sobria and S. saprophyticus after KA treatment were 0.4 mg/mL and 1.6 mg/mL, respectively. 1 × MIC KA showed unignorable antimicrobial activity against the two bacteria, leading to alterations in the bacterial physicochemical characteristics and cell death. Sub-MICs of KA can inhibit biofilm formation and decrease the metabolic activity and excretion of EPS, and these inhibition effects were in a dose-dependent manner. These results were further confirmed by the visual images obtained from scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Moreover, S. saprophyticus is more susceptible to KA in inhibiting biofilm formation, and for A. sobria, changes in the cell structure and the permeability of the cell membrane were more obvious. This research highlighted the antibacterial and antibiofilm activity of KA against A. sobria and S. saprophyticus .